2022
DOI: 10.1021/acs.jcim.2c01132
|View full text |Cite
|
Sign up to set email alerts
|

Computational Exploration and Characterization of Potential Calcium Sensitizing Mutations in Cardiac Troponin C

Abstract: Calcium-dependent heart muscle contraction is regulated by the cardiac troponin protein complex (cTn) and specifically by the N-terminal domain of its calcium binding subunit (cNTnC). cNTnC contains one calcium binding site (site II), and altered calcium binding in this site has been studied for decades. It has been previously shown that cNTnC mutants, which increase calcium sensitization may have therapeutic benefits, such as restoring cardiac muscle contractility and functionality post-myocardial infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…We thought the research on mechanisms of GHI based on ferroptosis and cuproptosis in treating MI/R injury was also condignly pondered. cTn I was one calcium-dependent subunit of cardiac troponin, whose level was equally diminished by GHI in our study [ 46 , 47 ]. Combining the corroboration that HSYA, CGA, and p CA were able to adjust the level of intracellular calcium, we inferred that the balance of cellular calcium ions probably was another mechanism of GHI in the therapy of MI/R injury because calcium overload also is one pivotal pathogenesis [ 48 51 ].…”
Section: Discussionmentioning
confidence: 79%
“…We thought the research on mechanisms of GHI based on ferroptosis and cuproptosis in treating MI/R injury was also condignly pondered. cTn I was one calcium-dependent subunit of cardiac troponin, whose level was equally diminished by GHI in our study [ 46 , 47 ]. Combining the corroboration that HSYA, CGA, and p CA were able to adjust the level of intracellular calcium, we inferred that the balance of cellular calcium ions probably was another mechanism of GHI in the therapy of MI/R injury because calcium overload also is one pivotal pathogenesis [ 48 51 ].…”
Section: Discussionmentioning
confidence: 79%
“…Dvornikov et al explored the effect of the R145W mutation on myofilament length-dependent activation (LDA) and found that the mutation does not affect LDA but does increase the sensitivity of the myofilament to Ca 2+ . Moreover, biochemical assays and functional experiments on the R145G mutation converged on the finding that this mutation causes an increase in myofilament Ca 2+ -sensitivity , and reduces the ability of cTnI to inhibit activation of cardiac muscle. , Computational efforts have also explored the effect that these cTnI mutations can have on the thermodynamics of the cTnC HP opening event. , Our lab and others have successfully shown the potential of computational tools as a viable option for studying cTn dynamics for the purpose of computationally aided drug discovery and Ca 2+ -binding simulations. …”
Section: Introductionmentioning
confidence: 99%